2021
DOI: 10.1111/ijlh.13463
|View full text |Cite
|
Sign up to set email alerts
|

How I investigate minimal residual disease in acute lymphoblastic leukemia

Abstract: Minimal Residual Disease (MRD) is the most important independent prognostic factor in acute lymphoblastic leukemia (ALL) and refers to the deep level of measurable disease in cases with complete remission by conventional pathologic analysis, especially by cytomorphology. MRD can be detected by multiparametric flow cytometry, molecular approaches such as quantitative polymerase chain reaction for immunoglobulin and T‐cell receptor (IG/TR) gene rearrangements or fusion genes transcript, and high‐throughput seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In addition to its laborious and time-consuming methodology, ASO-qPCR may be limited by the loss or emergence of new V(D)J sequences, leading to false negative MRD results. 38 …”
Section: Methods and Technical Aspects Of Measurable Residual Disease...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its laborious and time-consuming methodology, ASO-qPCR may be limited by the loss or emergence of new V(D)J sequences, leading to false negative MRD results. 38 …”
Section: Methods and Technical Aspects Of Measurable Residual Disease...mentioning
confidence: 99%
“…In addition to its laborious and time-consuming methodology, ASO-qPCR may be limited by the loss or emergence of new V(D)J sequences, leading to false negative MRD results. 38 In a study in which both BCR-ABL1 level and IG/TR ASO-qPCR were monitored in the bone marrow of Ph + B-ALL patients, overall concordance between the two methods was ~70%, 39 but IG/TR was found to be more reliable at predicting outcomes. However, another study investigating the discrepancy between the two methods showed that some patients with persistent BCR-ABL1 transcript levels may in fact contain the fusion gene in myeloid cells, indicating a chronic myeloid leukemia-like stem cell disease, which may be missed by ASO/qPCR.…”
Section: A Cmentioning
confidence: 99%
“…It is also used as a gating marker in flow cytometry (FCM) for diagnosis and residual disease detection posttreatment in B cell malignancies for the above reason. FCM is the most commonly used technique for detecting residual disease in ALL due to its advantage over molecular methods (Brüggemann & Kotrova, 2017; Correia et al, 2021). Currently, there are four groups of drugs that have been developed to target CD19, (i) unconjugated monoclonal antibodies like Inebilizumab and Tafasitamab, (ii) antibody drug conjugates like Denintuzumab mafodotin and Loncastuximab tesirine, (iii) molecules that recruit T cells to kill CD19+ cells by antibody dependent cellular cytotoxicity called bi‐specific T cell engager (BiTE) like Blinatumomab, and (iv) chimeric antigen receptor (CAR) T cell therapy like tisagenlecleucel, axicabtagene ciloleucel, and lisocabtagene maraleucel (Gambella et al, 2022; Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Precursor B-lymphoblastic leukemia (B-ALL) patients in morphologic remission may still have measurable disease detected by highly sensitive methods. The choice of an optimal method for MRD measurement depends on the test characteristics and clinical scenarios [2]. MRD values are reported to have a Center (RPCC) during the time from October 2020 to April 2022.…”
Section: Introductionmentioning
confidence: 99%